Beyond the Biomarker: Understanding the Diverse Roles of Human Epididymis Protein 4 in the Pathogenesis of Epithelial Ovarian Cancer - James, Nicole E.; Chichester, Clinton; Ribeiro, Jennifer R. (Frontiers in Oncology, 2018)
Human Epididymis Protein 4 (HE4) is an invaluable clinical biomarker, used for the detection of epithelial ovarian cancer (EOC). While much is known about the predictive power of HE4 clinically, far less has been reported about its molecular role in the progression of EOC. A deeper understanding of HE4’s mechanistic role may help contribute to the development of novel targeted therapies. This review summarizes what is collectively known about HE4 signaling and how it functions to promote tumorgenesis, chemoresistance and metastasis in EOC. Thus far, it has been difficult to recommend HE4 as a therapeutic target owing to the fact that its role in the progression of EOC has not been extensively evaluated. This review provides valuable insights that will have the potential to aide in the development of new HE4-targeted therapies.